Pelatihan Budidaya Hidroponik Sederhana Wick System Pada Skala Rumah Tangga Di Desa Tebang Kacang Kabupaten Kubu Raya - Zulfita, Dwi; Surachman, Surachman; Budi, Setia; Dupa Bandem, Putu (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
The point of the problem faced by the community, especially housewives in Tebang Kacang Village, Kubu Raya Regency, is that the need for agricultural products is increasing along with the increasing population, while increasing technological advances have shifted a lot of agricultural land which results in increasingly limited agricultural land. Such conditions require thinking and solutions to overcome them, one of which is the application of a hydroponic farming system. The solution to these problems is with a touch of science and technology, namely through extension activities on the meaning of hydroponic cultivation, quality and selling value of hydroponic cultivation products, being able to cultivate vegetables using a simple hydroponic Wick System and carry out product packing and product labeling. The method of implementing this training program includes orientation, socialization, dissemination of the technology of vegetable cultivation using the simple hydroponic Wick System, training on packing and product labeling and evaluation of activities to find out the obstacles / difficulties encountered during the activity to then find solutions in solving them. The results of the activity show that the level of understanding and desire for program sustainability in training and mentoring activities has increased by up to 75% regarding the manufacture of simple hydroponic vegetable cultivation using the Wick System method.